2022
DOI: 10.1038/s41598-022-16395-w
|View full text |Cite
|
Sign up to set email alerts
|

Mortality and biochemical recurrence after surgery, brachytherapy, or external radiotherapy for localized prostate cancer: a 10-year follow-up cohort study

Abstract: To compare the effectiveness at ten years of follow-up of radical prostatectomy, brachytherapy and external radiotherapy, in terms of overall survival, prostate cancer-specific mortality and biochemical recurrence. Cohort of men diagnosed with localized prostate cancer (T1/T2 and low/intermediate risk) from ten Spanish hospitals, followed for 10 years. The treatment selection was decided jointly by patients and physicians. Of 704 participants, 192 were treated with open radical retropubic prostatectomy, 317 wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 30 publications
0
7
1
Order By: Relevance
“…Guo et al deemed that BT offers oncological outcomes similar to RP in elderly patients with localized PCa. In a recent study, Suárez et al reported a comparative study of mortality and biochemical recurrence after RP, BT, or external radiotherapy for localized PCa patients at 10 years of follow-up, and BT presented high overall survival similarly to RP, but higher risk of biochemical progression [ 19 ]. These results were similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Guo et al deemed that BT offers oncological outcomes similar to RP in elderly patients with localized PCa. In a recent study, Suárez et al reported a comparative study of mortality and biochemical recurrence after RP, BT, or external radiotherapy for localized PCa patients at 10 years of follow-up, and BT presented high overall survival similarly to RP, but higher risk of biochemical progression [ 19 ]. These results were similar to our study.…”
Section: Discussionmentioning
confidence: 99%
“…1 Even among patients treated with definitive local therapy (prostatectomy or radiotherapy [RT]), approximately 30% will recur within 10 years, and a substantial fraction will develop metastases. 2…”
Section: Clinical Challenges In Evaluation and Treatmentmentioning
confidence: 99%
“…1 Even among patients treated with definitive local therapy (prostatectomy or radiotherapy [RT]), approximately 30% will recur within 10 years, and a substantial fraction will develop metastases. 2 Prostate cancer is highly dependent on androgen signaling for growth and survival. Withdrawal of testosterone via ACCOMPANYING CONTENT Article, p. 3595…”
mentioning
confidence: 99%
“…2 The BCR rate of brachytherapy (BT) ranges from 16% to 20%. 3,4 In addition, cryotherapy (CRYO) has emerged as a primary treatment option, especially in selected low-and intermediate-risk patients owing to its competitive oncological and excellent urinary continence outcomes. [5][6][7] The BCR rate after primary CRYO ranges from 20% to 40% based on Phoenix criteria.…”
Section: Introductionmentioning
confidence: 99%